ANALISA PENGARUH STRATEGI COPING STRES KERJA PADA STRAIN FISIK DAN PSIKIS (STUDI KASUS DI RUMAH SAKIT UMUM DI YOGYAKARTA) - Djamilah, Siti (Research Institution and Community Service Wijaya Kusuma Surabaya University, 2005)
This research examined the influence of occupational stress coping strategies on physiological and psychological strains. Specifically, this study analyzed the effectiveness of coping strategy which comprised: problem focused coping, emotion-focused coping, supervisor's support and co-worker's support (social support) and religiosity in maintaining physiological and psychological health. This research tested to nurses in one of general hospitals in Yogyakarta, because of the attribute of nurse profesion very suitable for the research of occupational sress. One hundred and ten questionnaires were distributed, 104 questionnaires returned and only 100 questionnaires were able to be used. Next step, the researcher examined validity and reliability testing which delivered independent variable: those were active coping and planning dimension as representation of problem focused coping; acceptance and denial as the representation of emotion focused coping; social support (supervisor and co-worker); religiosity that had close friend subject. Beside that, it delivered dependent variable that were physiological and psychological strains. Multiple regressions was used to examined the effect of four coping strategies toward physiological and psychological strains. Moreover it also used hierarchical regressions to prove the ability of problem focused coping to explained the bigger proporsion of physiological and psychological strains variance beyond the ability of three others. The result of multiple regressions indicated that the effect of four coping strategies toward physiological strains were not supported. In the other hand, The result of multiple regression proved that social support had influence on the decreasing of psychological strain. Beside that religiosity also gave influence on psychological strain, but into different direction that was increasing psychological strain. The result of hierarchical regressions showed that problem focused coping explained the bigger proporsion of psychological strain variance beyond the ability of three others.